Obstacles Faced by Palestinian Refugees in Accessing Health Services - Abdulaziz Albrithen; Qusai Ibrahim; Asmaa Ahmed (Social Work and Society, 2024)
Health equity is a right stipulated by United Nations charters and is a basic topic of interest in humanitarian assistance professions, including social work. The principles of health equity are based on achieving parity in the delivery and provision of human services and satisfying the health needs of disadvantaged individuals, groups, and communities. This study aims to understand the obstacles Palestinian refugees face in availing the health services provided by international relief agencies (e.g., UNRWA). Palestinian society is classified as a disadvantaged community by virtue of its political nature and humanitarian situation. This study conducts a social survey to assess the obstacles preventing the achievement of health equity among Palestinian refugee families living in Palestinian territories. The sample consisted of 600 Palestinian refugee families in Nablus, covering different geographical distributions. Furthermore, 121 social workers in a relief and social work program affiliated with UNRWA in the West Bank were surveyed. The findings suggest that Palestinian refugees face multiple disadvantages that curtail them from availing of healthcare facilities. The findings pertaining to the role of social work show that social workers have an important role in improving healthcare access.